2021
DOI: 10.1002/pbc.29243
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life, fatigue and health behaviours in Australian adolescent and young adult cancer survivors

Abstract: Introduction Current knowledge of the long‐term health behaviours and well‐being of adolescent and yong adult (AYA) cancer survivors is limited. The aim of this study was to evaluate the health behaviours of AYA cancer survivors compared to Australian normative data and describe their health‐related quality of life (HR‐QoL) and levels of fatigue. Method A cross‐sectional online survey of participants aged 15–25 years at diagnosis and 2–7 years post treatment completion was conducted at a comprehensive cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Previous studies in either older [32] or working-age adults with CKD [31] or in those with cancer [33] have reported weakness as a highly severe symptom. It impacts on younger adults with cancer in undertaking usual physical and social activities [3335], and it is likely that this impact also occurs in working-age adults with CKD (e.g., being unable to work). Weakness is known to be associated with other CKD symptoms such as anxiety, depression [32], pain [36], poor mobility, poor appetite, dyspnoea, drowsiness, and difficulty sleeping [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in either older [32] or working-age adults with CKD [31] or in those with cancer [33] have reported weakness as a highly severe symptom. It impacts on younger adults with cancer in undertaking usual physical and social activities [3335], and it is likely that this impact also occurs in working-age adults with CKD (e.g., being unable to work). Weakness is known to be associated with other CKD symptoms such as anxiety, depression [32], pain [36], poor mobility, poor appetite, dyspnoea, drowsiness, and difficulty sleeping [37].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer fatigue is a painful symptom that affects the functional part of young adulthood, where independence and social interactions are important. Moreover, it is a factor that can lower the overall QOL [42]. Implicit social isolation caused by being diagnosed with diseases requiring long-term treatment at a young age is exacerbated by fatigue, and the resulting stress can negatively affect the developmental stage of young adults who lack emotional control [43].…”
Section: Discussionmentioning
confidence: 99%
“…35 Unfortunately, physical activity decreases after cancer diagnosis for many AYAs 36 and over one third of AYA survivors do not meet physical activity guidelines. [36][37][38][39] Although data regarding predictors of physical activity are mixed, 40 higher income, 38 postsecondary education, 38 and gym access 37 have been associated with higher levels of physical activity, suggesting that resources and access may play a key role in this behavior. Available physical activity interventions for AYA survivors demonstrate limited efficay [41][42][43] and there is a critical need for additional physical activity intervention development, evaluation, and implementation efforts.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…48 Rates of tobacco use vary across countries and cohorts, with recent studies suggesting that 2%-33% of AYA survivors currently smoke cigarettes. 36,39,44,45,48 As tobacco companies continue to develop new flavors (eg, sweet/ fruity e-cigarettes), packaging, and delivery systems (eg, vaping devices), there remains a need to understand the use of these products among AYA survivors, particularly as a recent study of AYA survivors receiving care in Chicago found that over half had used one or more other nicotine products (hookah, 50%; cigar, 37%; little cigar, 32%; e-cigarette, 20%). 49 Unfortunately, behavior change techniques that drive smoking cessation intervention efficacy in general populations do not appear to improve outcomes among cancer suvivors.…”
Section: Substance Usementioning
confidence: 99%